Activity-based proteomic profiling: application of releasable linker in photoaffinity probes. Issue 1 (January 2020) - Wang, Jin; Chen, Qinhua; Shan, Yuanyuan; Pan, Xiaoyan; Zhang, Jie
Highlights: It presents an overview of photoaffinity label in exploring interaction of biomacro-molecules. PAL is a promising technique in analyzing the interaction between ligand and receptor. Combining releasable chemical crosslinking and PAL is an interdisciplinary proposal. Abstract : Combining releasable chemical crosslinkers with photoaffinity probes represents a valuable tool for identifying protein–protein interactions (PPIs). The biomacromolecule photoaffinity probe prepared by using releasable photoaffinity linkers can be used to exploring PPIs by triggering release of the releasable group. More importantly, it can overcome the shortcomings of macromolecular photoaffinity probes without label transfer functionality to accurately confirm defects in specific structural sites. It shows particular promise for research exploring the interaction of unknown proteins and transient–weak PPIs in living organisms to discover new drug targets. In this review, we highlight recent progress in the development and application of chemical releasable linkers in photoaffinity probes. Several comparative studies are described in which the efficiency of various photoaffinity probes are compared.